Pilot study to validate PIKE-based inferences at site level - Jachmann, Hugo (Pachyderm, 2012)
The primary objective of the Monitoring of Illegal Killing of Elephants (MIKE) programme is to monitor worldwide trends in elephant poaching. MIKE has been employing in its analyses the proportion of illegally killed elephants (PIKE) as a relative indicator of poaching levels. PIKE is subject to a number of potential biases that need to be understood to assess the validity of inferences made from analyses based on it. In four well-managed sites (Queen Elizabeth and Murchison Falls in Uganda, and Mole and Kakum in Ghana), a pilot study was carried out to examine the on-site reliability of PIKE. The detection probability of elephant carcasses was examined in relation to visibility (habitat types) on patrol, and PIKE results were compared with the results of a catch per unit effort (C/E) analysis. Due to sharply increased patrol coverage in three out of four sites, by 2011, the detection probability of elephant carcasses approached 1. PIKE, based on verified field data corrected for detection probability, compared well with data from the carcass sheets in the MIKE database. C/E results provided support for the on-site use of PIKE. Because the relationship between the C/E index and law-enforcement effort varied by site, which makes pooling of data complicated, for MIKE’s purposes C/E analysis was not considered a practical tool with which to monitor worldwide elephant poaching. PIKE data on the other hand can be easily pooled, and the pooling may erode away some of its imperfections. PIKE was found to be superior to C/E analysis for a system like MIKE. Additional key words: MIKE, elephant poaching, monitoring L’objectif principal du programme du Suivi de l’abattage illégal des éléphants (MIKE) est de faire le suivi des tendances mondiales du braconnage des éléphants. Dans ses analyses MIKE utilise la proportion des éléphants abattus illégalement (PIKE) comme un indicateur relatif du niveau de braconnage. PIKE est sujet à un certain nombre de partis pris potentiels. On doit comprendre ces partis pris afin d’évaluer la validité des conclusions faites à partir des analyses qui se basent sur PIKE. Sur quatre sites bien gérés (Queen Elizabeth et Murchison Falls en Ouganda, Mole et Kakum au Ghana), une étude pilote a été réalisée pour examiner la fiabilité de PIKE sur le site. La probabilité de détection des carcasses d’éléphants a été examinée par rapport à la visibilité (types d’habitats) en patrouille, et on a comparé les résultats de PIKE à ceux de l’analyse de la capture par unité d’effort (C/E). En raison de la forte intensification de la couverture de patrouille dans trois des quatre sites, jusqu’en 2011, la probabilité de détection des carcasses d’éléphants avoisinait 1. PIKE basée sur des données vérifiées, corrigée pour la probabilité de détection, s’est comparée bien aux fiches de carcasse dans la base de données de MIKE. Les résultats de l’analyse C/E ont appuyé l’utilisation de PIKE sur le site. Puisque la relation entre l’indice de l’analyse de C/E et l’effort de l’application de la loi variait selon le site, ce qui complique la mise en commun des données, pour les fins de MIKE, on ne considère pas l’analyse C/E d’être un outil pratiquepour surveiller le braconnage des éléphants dans le monde entier. D’autre part, on peut facilement mettre en commun les données de PIKE, et la mise en commun peut éroder certaines de ses imperfections. On a donc trouvé que PIKE était meilleure que l’analyse C/E pour un système comme MIKE. Mots clés supplémentaires: MIKE, braconnage des éléphants, monitoring